Innovations in thermal energy systems, bridging traditional and emerging technologies for sustainable energy solutions - Eze, Val Hyginus Udoka (Frontiers in Thermal Engineering, 2025)
IntroductionThermal energy systems (TES) have been foundational to global industrialization and power generation, with fossil fuel-based technologies providing nearly 81% of the global primary energy supply as of 2024. However, their dependence on finite resources and low conversion efficiencies, often below 40% in conventional steam power plants, has led to significant greenhouse gas (GHG) emissions, accounting for over 35% of global CO2 output. The urgent need for sustainable, efficient, and low-carbon alternatives has prompted transformative innovations in TES over the past two decades, particularly in hybridization and digital optimization.MethodsThis study employed the PRISMA methodology to systematically review 163 peer-reviewed articles published between 2004 and 2024. The analysis focused on trends and advancements in TES, including enhancements in Rankine cycle efficiency, deployment of advanced storage media such as phase change materials (PCMs), thermochemical options, nano-enhanced composites, and hybrid configurations integrating biomass, concentrated solar power (CSP), and photovoltaic-thermal (PVT) systems. Special emphasis was given to the role of digitalization, including artificial intelligence (AI), machine learning (ML), Internet of Things (IoT), and digital twin technologies in optimizing TES performance.ResultsThe findings reveal substantial progress in TES modernization. Digital tools enabled real-time optimization, predictive maintenance, and adaptive control, improving system efficiency by 20%-35% and reducing downtime by up to 40% in pilot projects. Waste heat recovery technologies, notably organic Rankine cycles (ORCs) and thermoelectric generators (TEGs), achieved energy recovery efficiencies exceeding 80% for low- to medium-grade heat streams. Modular and containerized TES solutions demonstrated effectiveness in decentralized applications, reducing post-harvest losses by up to 30% in agriculture and improving vaccine cold chain reliability in sub-Saharan Africa by over 50%. Furthermore, integration with electrochemical storage and green hydrogen pathways has positioned TES at the core of multi-vector decarbonized energy platforms.DiscussionThe review underscores that the future of TES will be defined by interdisciplinary research and development, advanced material innovation, particularly nanostructured composites, and supportive regulatory frameworks. Hybrid renewable integration and digitalization are central to achieving Paris Agreement goals, enhancing energy security, and promoting global energy equity. The transition toward intelligent, low-carbon thermal networks reflects not only technological evolution but also a paradigm shift essential for long-term sustainability.